1989
DOI: 10.1172/jci114043
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic regulation of the serum concentration of 1,25-dihydroxyvitamin D by phosphorus in normal men.

Abstract: We asked this question: in normal humans, is either a normal dietary intake or normal serum concentration of phosphorus a determinant of the serum concentration of 1,25(0H-)D? In seven normal men whose dietary phosphorus was decreased from 2,300 to 625 mg/d, each intake for 8-9 d, under strictly controlled, normal metabolic conditions, we measured serum concentrations of 1,25(OH)2D daily, and concentrations of phosphorus hourly throughout a 24-h period, before and after restriction. Decreasing dietary phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(109 citation statements)
references
References 37 publications
2
106
0
Order By: Relevance
“…There was no effect of phosphate on PTH in the second study. This was most likely due to the timing of the blood sampling, other studies have shown higher levels of serum phosphate and PTH after a meal (Calvo et al, 1990;Calvo et al, 1988;Portale et al, 1989). The dose of phosphate used in the second study was high, and was above the 2.5th percentile reported for British men of 2310 mgad (Gregory et al, 1990).…”
Section: Discussionmentioning
confidence: 80%
“…There was no effect of phosphate on PTH in the second study. This was most likely due to the timing of the blood sampling, other studies have shown higher levels of serum phosphate and PTH after a meal (Calvo et al, 1990;Calvo et al, 1988;Portale et al, 1989). The dose of phosphate used in the second study was high, and was above the 2.5th percentile reported for British men of 2310 mgad (Gregory et al, 1990).…”
Section: Discussionmentioning
confidence: 80%
“…Dietary phosphorus excess leads to reduced intestinal calcium absorption and 1,25-(OH) 2 D 3 production (Tanaka & Deluca, 1973;Portale et al, 1989;Rodriguez et al, 1991). Hyperphosphatemia, induced by a high-phosphorus diet in combination with low Ca intake, particularly common in women, is a major stimulus for PTH synthesis and secretion (Reiss et al, 1970;Prince et al, 1993;Nielsen et al, 1996).…”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…So, the Ca ++ level in blood may remain within limit due to secondary hyperparathyroidism. This PTH also causes phosphates diuresis effect on kidneys lowering the serum phosphate 7 . But in this case, she has phosphaturia, not due to secondary hyperparathyroidism as PTH level was normal, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Familial hypophosphatemic or XLH rickets is one of the most common non-nutritional rickets, though it is less reported among paediatric group 7 . Generally, it is the late onset disease, not common in toddler group, like nutritional rickets 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation